Terminal efficiency according to undergraduate degree of stomatology at the Universidad Peruana Cayetano Heredia, 1975-2018 - Girano-Arévalo, Angela (2021)
Obtaining the professional title is the last stage of professional training, however, each modality has its own characteristics, and therefore, its own terminal efficiency. Objective: Determine the terminal efficiency according to the degree modality of undergraduate graduates of the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia, Lima-Peru, from 1975 to 2018. Material and Methods: The research was retrospective based on records of undergraduate graduates according to the institutional repository of the university. The variables were degree modality, terminal efficiency and graduation decade. For the statistical analysis, the statistical program STATA 16.1 was used. Results: The research work presented the lowest terminal efficiency with an average of 1.01 years (SD = 0.10) and with a frequency of 98.97% (n = 96) Up to 1 year, being statistically significant (p <0.05). Conclusions: The research work presented better terminal efficiency in undergraduate graduates of the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia, Lima-Peru, from 1975 to 2018.